Um modelo de maturidade em gestão de processos para o Poder judiciário - Garcia, Herbert Eduardo de Goes (2018)
Purpose – Since the publication of the Constitutional Amendment number 45, in 2004, the National Council of Justice (CNJ) was created, with assignments, among others, of administrative control of the Judiciary. Since then, the CNJ has brought techniques and management tools aiming the modernization of the administrative machine of the Judiciary. With the goal of forming a more efficient, effective and actual management framework, the CNJ has been encouraging courts to absorb techniques such as Strategic Planning, Project Management, Risk Management, Process Management, among others. This last one, when well established and structured with the other techniques, has been successful in the private sector. However, regarding the target sector of the research, the Federal Justice, as the documentary research has shown, the Process Management has not advanced enough to generate impact on the jurisdictional accountability and, therefore, in its institutional mission. The objective of the present study is to propose a maturity model in process management for that sector of Justice. The proposed model was built from a wide bibliographical research of the metamodels in Process Management and, using the most referenced models in the academic literature, a customization of these was carried out from a field research in the federal courts. The result was an applicable maturity model, with the appropriate adaptations, for any sector in Justice, capable of guiding the organization on the path of searching its maturity in the Process Management. Design/methodology/approach – As to the purposes, a Methodological research. As for the means, a survey of mixed or multiple methods. Findings – A business process management maturity model for Judiciary. Research limitations/implications (if applicable) – It lacks empirical validation as a benchmarking instrument. Practical implications – It can be used in any body of the Judiciary as an instrument for measuring maturity, routing of expenses with maturity of process management and benchmarking. Social implications (if applicable) – Potential improvement of the business processes of the organizations of the Judiciary.